Efficiency enhancement in scintillation detectors by changing the valence‐band electron density and crystal structure of the scintillation material. Issue 3 (22nd April 2022) - Couch, Caitlynn; Halliwell, Elijah; Begum, Rahima; Ali, Ghafar; Khan, Tahirzeb; Maqbool, Muhammad
Abstract : Changing the crystal structure of scintillation materials changes the valence‐band electron density, which enhances the efficiency of scintillation detectors. This will enhance the image quality of all imaging techniques based upon scintillation detectors. Abstract : Scintillation detectors are commonly used for detecting radiation in various situations. NaI:Tl, CsI:Tl, BaF2 and CaF2 :Eu are a few compounds that act as scintillation crystals for these detectors. The efficiency of a scintillation detector is one of the most important factors in improving the detector's performance. The present work shows that the efficiency of a scintillation detector can be increased by increasing the valence‐band electron density as a result of changing the crystal structure of the scintillating material. This will enhance the image quality of all imaging techniques based upon scintillation detectors. The results reveal that by changing the structure of the crystal from simple cubic to body‐centered cubic or face‐centered cubic the efficiency of the detector increases. The packing of more atoms into the crystal increases the number of atoms per unit cell and the density of the crystal. It is also observed that the increase in the number of atoms per unit cell and the density of the crystal will equally increase the efficiency of the detector. The additional atoms from changing the crystal structure contribute more valence‐band electrons, which allows for a higher chance of interaction between the incoming radiation and the valence‐band electrons to absorb more radiation energy.